Genetic variability and advance, heritability, Path coefficient analysis and inter-characters relationships in colocynth (Citrullus colocynthis [L.] Schrad.) collected in Southeastern villages of Benin Republic - Zanklan, A. Seraphin (European Scientific Journal, ESJ, 2024)
Genetic improvement of crops for important traits requires reliable estimates of genetic variability. heritability and genetic advance of intending parent materials to identify traits useful in planning an efficient breeding program through selection. Effectiveness of genetic improvement of a crop depends on the variability in the agro-morphological traits of individual genotype. Understanding the variation that exists will allow the breeder to determine the breeding strategies to adopt in his breeding program. The objectives of the study were to estimate the magnitude of genetic variability and advance, heritability, inter-characters relationships by simple correlations and path coefficient analysis for yield contributing traits of 40 local colocynth genotypes cultivated in Southeastern Benin. The experiment was carried out in a randomized complete block design with three replications in three locations and during three years. 34 morpho-agronomic traits were observed in each genotype. Analysis of variance revealed that effects of genotype, genotype by year or location and genotype by year by location interactions were significant (p ≤ 0.01 or 0.05) for all the characters. PCV values were relatively greater than GCV for all traits. High magnitude of phenotypic and genotypic coefficient of variations as well as high heritability along with high genetic advance were recorded particularly for qualitative traits. Correlation and path coefficient analysis were performed on all 34 traits. It was found that all of the yield components except time to emergence, time to tailspins, leaf limb width, fruit number per plant, fruit width, seed length, seed tegument percentage and stem pubescence texture had significant and positive correlations with yield attributes represented by thousand-seeds weight (TSW) and seed number per plant (SNP). Path coefficient analysis indicated that all the characters (except leaf pubescence texture, stem pubescence texture, fruit design produced by secondary color and male flower size) had positive direct effect on TSW and partly SNP. Results suggested that most of the 34 quantitative and qualitative traits studied could be effectively used as selection criteria in the breeding program of Citrullus colocynthis varieties with high yielding.